The investigation of establishing green roof infrastructure in Iran's Metropolitans / Mojtaba Valibeigi and Mehdi Abdullahi - Valibeigi, Mojtaba; Abdullahi, Mehdi (2012)
This article studies the effective factors in the development of green roofs in Iran based on Hierarchical Analysis. Due to the high value of land in the main cities of Iran especially Tehran and the low capitations of green spaces;the use of green roof and its dependent technology can be a good selection to arrive at green government goals. Hierarchical Analysis was used in this study to show the 6 main axes in the development of green roofs that the fund sources. Economic issues, policies and organizational management were the most important factors followed by legal aspects, technical and scientific infrastructure, cultural environment and geographical environment. The subsequent processes were the determination of effective factors in subgroups and the formulation of a final synthesis of administrative actions and a performance sensitivity analysis diagram. Based on these, most problems in development green roofs in Iran were identified as higher costs to conventional roofs, lack of legal frameworks, low energy costs in Iran and other factors which were described in details. Finally according to available issues, the green roof development needs to determine the policies and strategies and hence provide the necessary infrastructures, incentives and legal administrative actions coupled with public participation and skilled manpower to maximize the use of sector capacities in this field.